Análise preliminar de viabilidade do processo de consolidação mecânica acelerada em rejeito de bauxita de uma mina em Juruti - PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
One of the main challenges facing mining companies today is the search for harmonious development between operational efficiency and environmental preservation. The growing mobilization around new processes based on the principles of circular economy and sustainability has encouraged the development and application of new techniques for handling bauxite tailings. This research seeks to reproduce the bauxite tailings sedimentation process in the laboratory, with the aim of analyzing the water retained in the thickened tailings layer. In addition, the study aims to evaluate the effectiveness and viability of the Accelerated Mechanical Consolidation (AMC) method for the management and treatment of bauxite tailings, by building a simulation prototype in a laboratory environment. With regard to sedimentation, slurries of different concentrations (6%, 9%, 12% and 20%) were simulated in test specimens. The results indicated an average of 42,64% solids by mass in the layer of sedimented material. In order to recover this water, the study focused on the application of AMC to pulps with different solids concentrations (30%, 40%, 50% and 60%), observing the efficiency of water recovery and the increase in the concentration of solids in the pulp. The results indicate that AMC is effective in recovering retained water and the concentration of solids, with a recovery of around 20% of the water in pulps with 30% solids, offering an efficient alternative to tailings management. Pulps with concentrations above 50% showed an unfavorable ratio due to the low percentage of water recovered (<1%). The preliminary study concludes that accelerated mechanical consolidation is an alternative for treating bauxite tailings, with the potential to optimize the dewatering process and reduce the environmental impacts associated with tailings disposal.
Keywords: Gerenciamento do rejeito; Sedimentação; Recuperação de água; Sustentabilidade; CNPQ:: CIÊNCIAS EXATAS